Effect of Muscle Action on the Kinetic and Kinematic Behavior of the Barbell during Isoinertial Strength Assessment - Garnacho Castaño, Manuel Vicente; Hernández Lougedo, Juan; García Fernández, Pablo; Maté Muñoz, José Luis (My University, 2021)
An isoinertial strength assessment was performed to examine the kinetic and kinematic behavior of the barbell during several muscle actions. Velocity¿time characteristics, force¿time relationship, one repetition maximum (1RM), power output, and acceleration were compared in eccentric¿concentric (EC) versus concentric only (C) sequences of the bench press (BP) and military press (MP). In two separate sessions, 28 and 29 resistance-trained athletes executed EC or C sequences in random order of the BP and MP, respectively, in an incremental load test up to their 1RM. Higher values were recorded in BP-EC than in BP-C, MP-EC, or MP-C (p < 0.01) for peak acceleration, peak rate of force development, peak rate of velocity development, and power output. Significant differences were detected between exercises in terms of the portion of the concentric phase (%) at which peak acceleration was detected, or acceleration up until peak velocity was observed (p < 0.05). No differences were observed between exercises in the portion of the concentric phase where acceleration up to the braking phase took place. The eccentric muscle action prior to concentric movement was a key factor to enhance the kinematic and kinetic performance in BP exercise. No such effects of the countermovement were produced in MP